Pathogenesis of haematogenous spread in Acanthamoeba castellanii infections - Edwards-Smallbone, James (2013)
Acanthamoeba castellanii is an amoeboid protozoan which causes opportunistic infections, including granulomatous encephalitis in immune-compromised patients. Haematogenous dissemination follows initial infection and the pathogen exhibits an ability to cross the blood-brain barrier (BBB). In the bloodstream and at the site of BBB penetration in the brain microvasculature A. castellanii is exposed to host humoral immunity. Here, we have provided insights into A. castellanii pathogenesis and the identity of amoeba antigens participating in immune control. We have investigated the role circulating immunoglobulin plays in preventing penetration of the BBB, and whether trophozoites can alter the efficacy of the immune response. Furthermore we have extended previously published data, demonstrating that amoeba proteases can degrade all antibody classes including physiologically-derived antibody. Nonspecific binding of polyclonal antibody was also observed, and attributed to Fc-binding activity by trophozoites. Additionally, we have examined the binding dynamics of A. castellanii under physiological conditions. BBB disruption was shown to be not directly linked to binding, instead it is reliant on secreted proteases. This study provides insights into mechanisms by which A. castellanii evades host immunity and crosses the BBB. This has the potential to enhance therapeutic strategies aimed at restoring essential disease prevention processes. In addition we have identified a number of amoeba antigens that are targets for the immune system and which may therefore be exploited through vaccination or immunotherapy.